SIKAP DAN INTENSI PEMANFAATAN INTERNET DALAM KEGIATAN BISNIS - Anggita Nurul Adha, Irena; Virianita, Ratri (Sodality: Jurnal Sosiologi Pedesaan, 2010)
As developed time, needs of information and communication media become significant. Internet utilization functions for business were transformed from information exchange into an instrument for business strategy application such as marketing, selling and customer service. In general, internet has three functions in business such as communication, promotion and research. Small and middle scale entrepreneur which exposed with the growth of information technology have the options whether to utilize internet for business or not. The objective of this study is to describe attitude and intention of internet utilization for business, and to analyze the effect of attitude and subjective norm to intention of internet utilization for business on small and middle scale entrepreneur. This research used quantitative approach. The results of this study is, mostly small and middle scale entrepreneur have positive attitude and intention to internet utilization for business. Attitude and subjective norm are effected to intention to internet utilization for business.